2020
DOI: 10.4103/jfmpc.jfmpc_811_20
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge & awareness of burn first aid among health-care workers in Saudi Arabia: Are health-care workers in need for an effective educational program?

Abstract: Objective: The objective of this study was to assess the level of awareness and knowledge of first aid for burns among healthcare workers in Saudi Arabia. Methods: We conducted a cross-sectional study between September 2 and December 5, 2019, via a self-administered online questionnaire among healthcare workers at a university hospital. The questionnaire comprised 24 questions divided into two sections pertaining to demographics and first aid for burns. This study was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 17 publications
1
22
1
1
Order By: Relevance
“…Fast and prompt management of burns is essential for a better outcome of burned subjects. Therefore, appropriate first aid treatment can decrease significantly the situation of the burns and enhance the survival from the burn [17,18,19]. Community awareness progrmames for first aid burn injuries towards the general population have a great impact on educating peple towards how to react to burn injuries [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fast and prompt management of burns is essential for a better outcome of burned subjects. Therefore, appropriate first aid treatment can decrease significantly the situation of the burns and enhance the survival from the burn [17,18,19]. Community awareness progrmames for first aid burn injuries towards the general population have a great impact on educating peple towards how to react to burn injuries [20].…”
Section: Discussionmentioning
confidence: 99%
“…Among Medical Students, King Khalid University in Abha and Princess Norah University in Riyadh, studies showed poor knowledge about first aid among the medical students [15][16][17]. Even among health care providers, Studied reported limited knowledge of burn first aid with several using of traditional remedies [18,19]. Training can help in burn management as trained students in Secondary School in Taif showed better deal with emergency situations compared to untrained students [20].…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire was formulated based on our study's objectives and available questionnaire with similar objectives [ 1 ]. A language translation specialist translated the questionnaire into Arabic.…”
Section: Methodsmentioning
confidence: 99%
“…Burn-related injuries occur when one or more of the skin's layers ruptures by hot liquids, hot solids, or a flame. Additionally, 'burn' is a term used to describe damage to the skin brought on by radiation, electricity, or chemicals [ 1 ]. Burn injuries are among the most expensive and catastrophic public-health issues because of the severe physical, functional, and psychological effects [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first aid for burns field was not sufficiently understood or perceived by the healthcare professionals, despite their good attitudes toward it. Additionally, Hatan Mortada 2020 reaffirmed the need for an efficient educational program for healthcare professionals to improve their knowledge and comprehension of first aid for burns, which would subsequently boost the success and availability of the best possible care for the patients [10].…”
Section: Introductionmentioning
confidence: 99%